Changes in the multidisciplinary management of rectal cancer from 2009 to 2015 and associated improvements in short‐term outcomes. (1st July 2019) - Roxburgh, C. S. D.; Strombom, P.; Lynn, P.; Cercek, A.; Gonen, M.; Smith, J. J.; Temple, L. K. F.; Nash, G. M.; Guillem, J. G.; Paty, P. B.; Shia, J.; Vakiani, E.; et al.
Abstract: Aim: Significant recent changes in management of locally advanced rectal cancer (LARC) include preoperative staging, use of extended neoadjuvant therapies and minimally invasive surgery (MIS). This study was aimed at characterizing these changes and associated short‐term outcomes. Method: We retrospectively analysed treatment and outcome data from patients with T3/4 or N+ LARC ≤ 15 cm from the anal verge who were evaluated at a comprehensive cancer centre in 2009–2015. Results: In total, 798 patients were identified and grouped into five cohorts based on treatment year: 2009–2010, 2011, 2012, 2013 and 2014–2015. Temporal changes included increased reliance on MRI staging, from 57% in 2009–2010 to 98% in 2014–2015 ( P  < 0.001); increased use of total neoadjuvant therapy, from 17% to 76% ( P  < 0.001); and increased use of MIS, from 33% to 70% ( P  < 0.001). Concurrently, median hospital stay decreased (from 7 to 5 days; P  < 0.001), as did the rates of Grade III–V complications (from 13% to 7%; P  < 0.05), surgical site infections (from 24% to 8%; P  < 0.001), anastomotic leak (from 11% to 3%; P  < 0.05) and positive circumferential resection margin (from 9% to 4%; P  < 0.05). TNM downstaging increased from 62% to 74% ( P  = 0.002). Conclusion: Shifts toward MRI‐based staging, total neoadjuvant therapy and MIS occurred between 2009 and 2015. Over the same period, treatment responses improved, and lengths of stay and the incidence of complications decreased.